ChemInform Abstract: Broadening the Chemical Scope of Laccases: Selective Deprotection of N‐Benzyl Groups. Issue 38 (3rd September 2015) - Martinez‐Montero, Lia; Diaz‐Rodriguez, Alba; Gotor, Vicente; Gotor‐Fernandez, Vicente; Lavandera, Ivan
Abstract Laccase from Trametes versicolor along with TEMPO is found to be a very efficient catalytic system for the deprotection of N‐benzylated primary amines using oxygen as a mild oxidant in aqueous medium.